Graphene-modulated assembly of zinc phthalocyanine on BiVO4 nanosheets for efficient visible-light catalytic conversion of CO2. Issue 36 (2nd April 2020) - Bian, Ji; Feng, Jiannan; Zhang, Ziqing; Sun, Jiawen; Chu, Mingna; Sun, Ling; Li, Xin; Tang, Dongyan; Jing, Liqiang
Abstract : Graphene-modulated ZnPc/BiVO4 Z-scheme heterojunctions for efficient visible-light catalytic CO2 conversion are achieved by increasing the optimized amount of highly dispersed ZnPc. Abstract : Ultrathin zinc phthalocyanine/graphene/BiVO4 heterojunctions have been successfully synthesized for efficient wide visible-light catalytic conversion of CO2 to CO with 14-time photoactivity improvement compared to the bare BiVO4 nanosheet, attributed to the strengthened Z-scheme charge transfer and separation by increasing the optimized amount of highly dispersed ZnPc via the pre-modified graphene-modulated assembly.